The Existing Method to Assess the Disease Incidence of Bacteria Leaf Blight and Its Effect to Rice Yield to Support the Indonesian Agriculture Insurance - Alit Susanta Wirya, Gusti Ngurah; Satya Andrayuga, Made; Sudiarta, I Putu; Shishido, Masahiro; Hongo, Chiharu (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 15 No 3 (2021): Vol.15, No.3, 2021, 2021)
Bacterial leaf blight (BLB) has become a major obstacle and a limiting factor in national rice production. Basically, this disease is caused by the bacterium Xanthomonas oryzae pv. oryzae. Therefore, to minimize the risk of disease infection to yield lost; The Ministry of Agriculture of the Republic of Indonesia has the agriculture insurance program. To support the program, the observations of disease incidence of the disease using existing method are needed. The purpose of this study was to determine the development of bacterial leaf blight on rice plants in Subak Munggu and to determine the effect of bacterial leaf blight on the yield of rice plants. Research activities included (1) isolation of pathogens from symptomatic leaves of rice plants, (2) weekly observations (3) morphological identification of pathogens (4) yields analysis. The results of this study showed the development of bacterial leaf blight in Subak Munggu, Munggu Village, Mengwi Sub-district, Badung Regency for ten weeks. The yield by calculating the weight of grains in each plot was calculated, it can be concluded that a sample that showed a high percentage of disease at the harvest time will cause the low grain yield production.